2020
DOI: 10.4103/jcar.jcar_6_20
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epidermal growth factor receptor T790M mutation by allele-specific loop mediated isothermal amplification

Abstract: INTRODUCTION: Targeted therapy using specific inhibitors against tyrosine kinases (TKs) is a paradigm in non-small-cell lung cancer management. However, the success of TK inhibitor (TKI) therapy depends on certain activating or acquired mutations, which render sensitivity or resistance to TKIs in the patients. The acquisition of epidermal growth factor receptor (EGFR) T790M point mutation is the most common mechanism of resistance to TKI in non-small cell lung cancer. A number of molecular strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Here we demonstrate a compact AS-Mini-LAMP + USS mutant speci c reaction that consists of 6-primers (FIP, BIP, F3, B3, USS FB, USS BB) spanning 155 bp, within the typical range of plasma cfDNA. In contrast to alternative mutation-selective LAMP design strategies (PNA-LNA-LAMP 11 and AS-LAMP/CF-LAMP 13,14 ) selectivity is encoded at the terminal 5' position of both the FIP and BIP primers, promoting selective self-primed exponential ampli cation upon self-hybridisation and loop formation from the FIP and BIP initiated reactions. Using synthetic template models, the mutant selective reaction (AS-Mini-LAMP Mut + USS WT ) demonstrated analytical sensitivity of 500 copies of mutant DNA within 25 minutes, > 20 minutes ahead of non-selective WT template.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we demonstrate a compact AS-Mini-LAMP + USS mutant speci c reaction that consists of 6-primers (FIP, BIP, F3, B3, USS FB, USS BB) spanning 155 bp, within the typical range of plasma cfDNA. In contrast to alternative mutation-selective LAMP design strategies (PNA-LNA-LAMP 11 and AS-LAMP/CF-LAMP 13,14 ) selectivity is encoded at the terminal 5' position of both the FIP and BIP primers, promoting selective self-primed exponential ampli cation upon self-hybridisation and loop formation from the FIP and BIP initiated reactions. Using synthetic template models, the mutant selective reaction (AS-Mini-LAMP Mut + USS WT ) demonstrated analytical sensitivity of 500 copies of mutant DNA within 25 minutes, > 20 minutes ahead of non-selective WT template.…”
Section: Discussionmentioning
confidence: 99%
“…With only a single base pair difference at their 5' terminal FIP and BIP primers, our data reinforce the intricacies of LAMP and requirement for design and testing of multiple primer sets. Arjuna et al, 13 similarly observed that only one of six primer sets could accurately distinguish between wild type and mutated DNA for detection of the EGFR T790M point mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation